2008
DOI: 10.1021/ol8016403
|View full text |Cite
|
Sign up to set email alerts
|

7-Silylcycloheptatrienes and Analogues: Reactivity and Selectivity in Cascade Processes

Abstract: 7-Silyl- and 7-silylmethylcycloheptatrienes react with acylnitroso reagents at room temperature to provide the corresponding silyl- and silymethylnorcaradiene cycloadducts. Depending on the reaction conditions, 7-silylmethylcycloheptatriene was also shown to provide, through cascade processes, functionalized cyclohexa-1,3-dienes or bicyclic synthons, incorporating one and two amino groups, respectively, that may be elaborated further, for instance, into sugar mimics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…Cycloadditions of silylcycloheptatrienes 4 a – b with acylnitroso reagents : The synthesis of silylcycloheptatriene precursors 4 a – b was carried out through direct silylation of tropylium tetrafluoroborate using (PhMe 2 Si) 2 Zn13 or the Grignard reagent Me 3 SiCH 2 MgBr 14. During our preliminary investigations,12 we observed that highly reactive acyl nitroso reagents15 efficiently trapped the norcaradiene valence isomer of 4 a and 4 b , to provide the resulting cycloadducts 5 a – b and 6 a – b in good yield as a single diastereoisomer, regardless of the reaction conditions or which nitroso reagent was used (Scheme ). Structures of 5 and 6 were assigned through 1 H NMR analysis and X‐ray diffraction studies, which established unambiguously that the reactivity of 4 a and 4 b in the cycloaddition processes is expressed through the norcaradiene form.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cycloadditions of silylcycloheptatrienes 4 a – b with acylnitroso reagents : The synthesis of silylcycloheptatriene precursors 4 a – b was carried out through direct silylation of tropylium tetrafluoroborate using (PhMe 2 Si) 2 Zn13 or the Grignard reagent Me 3 SiCH 2 MgBr 14. During our preliminary investigations,12 we observed that highly reactive acyl nitroso reagents15 efficiently trapped the norcaradiene valence isomer of 4 a and 4 b , to provide the resulting cycloadducts 5 a – b and 6 a – b in good yield as a single diastereoisomer, regardless of the reaction conditions or which nitroso reagent was used (Scheme ). Structures of 5 and 6 were assigned through 1 H NMR analysis and X‐ray diffraction studies, which established unambiguously that the reactivity of 4 a and 4 b in the cycloaddition processes is expressed through the norcaradiene form.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that a silicon group can be regarded as a masked hydroxyl group,11 which is crucial in this context because OR and a SiR 3 substituents should influence the above equilibrium with adverse effects. During our preliminary studies, we discovered during acyl nitroso cycloadditions onto cycloheptatrienes I (Figure 1), an unusual domino process leading, after further functionalization, to carbasugar type products 12. In this report, we provide a full account of our work and describe an extension to cycloaddition reactions involving aldehydes and ketones.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The reduction of 1,2,4-triazole ketoximes in the presence of baker's yeast leads to secondary triazole alcohols [51]. The synthesis of the respective hydroxylamines [52] or amines [53,54] is easily realized by the reduction of 1,2-and 1,3-oxazine ketoximes in the presence of NaCNBH 3 [52] or LiAlH 4 [54]. Hydrogenation of the oxime group of 1,2-thiazine ketoximes in the presence of Raney nickel in acetic acid gives primary amines [55].…”
Section: Transformations Of the Oxime Groupmentioning
confidence: 99%
“…one order of magnitude more tightly to E. coli 16S rRNA (K d = 6 ± 0.5 mM) compared to human 18S rRNA (K d = 68 ± 6.9 mM). 2 Additionally, 2,3,4-trihydroxycyclohexane-trans-1,5-diamines (e.g., 4) have been prepared as sugar mimics, 3 and 2-hydroxycyclohexane-trans-1,5-diamines (e.g., 5) have been utilized as intermediates in the synthesis of CC chemokine receptor 2 antagonists. 4 We herein report the synthesis of a series of hydroxydiaminocyclohexanes from the readily available 5 tricarbonyl(cyclohexadienyl)iron(1+) cation.…”
mentioning
confidence: 99%